OPTIMIZING BRAND AWARENESS BY USING FACEBOOK ADS AT BINA POTENSI ANAK INDONESIAN SCHOOLS - Muhammad Hilmyansyah; Noviandi Noviandi (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2021)
The development of social media today makes changes to marketing methods. Marketing using social media is a cheap solution and does not pose a high risk for the users. With social media, it can be used a way to increase brand awareness. An effective digital marketing media is needed to increase brand awareness, one of them is Facebook ads. In the education sector, facebook ads are still rarely used, generally schools use conventional marketing methods, this method has weaknesses, such as: limited scope and inefficient marketing costs. Marketing used conventional methods is considered ineffective, it occur at out by BPAI School in 2019 only 10% of potential consumers contacted the school. The small number of marketing effectiveness is the influence of the low brand awareness of the BPAI School, therefore innovation is needed in marketing to increase brand awareness, it is by using facebook ads. The results of the implementation of facebook ads at BPAI School for 5 days concluded that facebook ads had significant effect in increasing brand awareness